Node-based soft object deformation using stress estimation method - Mohd Nadzeri, Omar; Zhong, Yongmin (Springer, 2022)
Modeling of soft object deformation was dominated by the Mass Spring Method (MSM) and the Finite Element Method (FEM). Both methods require the discretization of a soft object into interconnected elements. The ele-ment-based deformation, however, has several weaknesses, such as it requires high computational costs to mesh the object, difficulty in handling topological changes, and complex mathematical calculations to describe the interconnected elements. This paper presents an initial investigation to address such deficiencies through a node-based approach associated with a stress estimation method. When a soft object is subjected to a load, the induced stresses at each node can be esti-mated using the Boussinesq equation. The estimated induced stress is then con-verted into movements based on the principle of energy conservation. The simu-lation model was developed in the MATLAB software. Simple deformation can be simulated with a high similarity to the FEM model generated by ABAQUS software. In terms of time performance, the proposed method clocked a slightly higher computational time with a difference of 1.0 s compared to the FEM model. Nevertheless, the findings show a promising performance of the proposed method.